(untitled) (Herald of Journalism, 2022)
The technological component is now freely and intensively penetrating the format of modern journalism. New concepts and methods have emerged. The nature of mass media has changed, a synthetic, multifunctional world is systematically demonstrated in the information space. Now the journalistic community has come close to perceiving the world of nature and the social environment through the lenses of pluralistic scientific knowledge. It is clear that new thinking in journalism is based not only on today’s situational novelty, but its historical roots go back to the distant past. Hence, the relevance and continuity of the ideas of ancient thinkers and modern scientists about the origin of facts, events and phenomenon starts from there. The main idea and the subject of this academic article are the study of nature and the origin of the fact as such. Scientific and practical significance of research work: the authors of the article seek to trace the course of the origin of the organic matter of the fact, as the primary microelement in the formation of stage information. For the maximum disclosure of the topic, the methods of general scientific interpretation (comments), comparative analysis, description and empiricism (meta-analysis) were used. In the course of the study, new results on the natural and artificial nature of information were achieved, the structure of matter objects was integrated with facts, and original graphic drawings of global communicative consciousness a modern system of mass media were born. Thanks to this study, in our opinion, the conceptual complex of journalism will be enriched, its scientific potential will increase, and the spatial range will expand. This article will pave the way to new research areas. New theoretical concepts will be introduced in the field of scientific journalism, analytical journalism and multimedia journalism. New research will be carried out in such areas of journalism as factology, textbooks in this new field will be issued. Keywords: fact, genome, quantum, mega-world, macro-world, micro-world, returning of time.